Quasiparticle effective mass of the three-dimensional fermi liquid by quantum Monte Carlo - Azadi,S; Drummond,ND; Foulkes,WMC (Physical Review Letters, 2021)
According to Landau's Fermi liquid theory, the main properties of thequasiparticle excitations of an electron gas are embodied in the effective mass$m^$, which determines the energy of a single quasiparticle, and the Landauinteraction function, which indicates how the energy of a quasiparticle ismodified by the presence of other quasiparticles. This simple paradigmunderlies most of our current understanding of the physical and chemicalbehavior of metallic systems. The quasiparticle effective mass of thethree-dimensional homogeneous electron gas has been the subject of theoreticalcontroversy and there is a lack of experimental data. In this work, we deploydiffusion Monte Carlo (DMC) methods to calculate $m^$ as a function of densityfor paramagnetic and ferromagnetic three-dimensional homogeneous electrongases. The DMC results indicate that $m^$ decreases when the density isreduced, especially in the ferromagnetic case. The DMC quasiparticle energybands exclude the possibility of a reduction in the occupied bandwidth relativeto that of the free-electron model at density parameter $r_s=4$, whichcorresponds to Na metal.